2023
DOI: 10.1259/bjr.20220108
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on brain magnetic resonance imaging (MRI) in adults: a review of imaging spectrum, clinical significance, and management

Abstract: Utilization of brain MRI has dramatically increased in recent decades due to rapid advancement in imaging technology and improving accessibility. As a result, radiologists increasingly encounter findings incidentally discovered on brain MRIs which are performed for unrelated indications. Some of these findings are clinically significant, necessitating further investigation or treatment and resulting in increased costs to healthcare systems as well as increased patient anxiety. Moreover, management of these inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Prevalence of incidental findings on brain magnetic resonance imaging (MRI) has been reported in the range of 9 to 54%, often in the range of 20 to 30%. [70][71][72] In a study of patients with functional seizures, approximately 50% of brain MRIs demonstrated incidental abnormalities, and 23% demonstrated incidental findings that could be associated with epilepsy, possibly leading to diagnostic confusion. 73 Encountering incidental findings is likely to occur when evaluating patients with FMD, and an approach to managing this is necessary.…”
Section: Investigations Commonly Performed Investigationsmentioning
confidence: 99%
“…Prevalence of incidental findings on brain magnetic resonance imaging (MRI) has been reported in the range of 9 to 54%, often in the range of 20 to 30%. [70][71][72] In a study of patients with functional seizures, approximately 50% of brain MRIs demonstrated incidental abnormalities, and 23% demonstrated incidental findings that could be associated with epilepsy, possibly leading to diagnostic confusion. 73 Encountering incidental findings is likely to occur when evaluating patients with FMD, and an approach to managing this is necessary.…”
Section: Investigations Commonly Performed Investigationsmentioning
confidence: 99%
“…Several other neuroradiological studies in healthy samples have reported incidental findings on MRI scans, though with substantial variation in the observed prevalence of observation. A recent review of these suggests that in non-clinical adult samples, the prevalence of incidental neurological findings ranges between 9 and 54% [ 4 ]. Thus, some levels of neurological ‘abnormality’ is relatively normal.…”
Section: Neurological and Cognitive Diversitymentioning
confidence: 99%
“…This is because children with neurological disease, learning disability, and emotional or attentional disorders were excluded from the sampling. It is also worth noting that, despite such exclusions, and as described above, many people have neurological findings that they are unaware of, perhaps at levels of over a quarter of the population [ 4 ]. Consequently, the normative samples inevitably do contain much data from individuals with neurological disorders.…”
Section: (Un)representativeness Of Samplesmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), a non-ionizing radiation medical imaging technology [1] is widely utilized in medical procedures. However, the extensive data collection required for one image as necessitated by the Nyquist criterion [2], makes the process time-consuming, constrained by technical and physiological limitations [3] since more samples are needed for optimal resolution.…”
Section: ░ 1 Introductionmentioning
confidence: 99%